Place the indicated product in the proper location on the grid.
(2x - 3y )(4x - y )

Andrew.|Points 61733|

Question|Asked by ardonav23

Asked 3/23/2016 9:25:32 AM

Updated 3/23/2016 11:46:16 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by Venen [3/23/2016 11:44:23 PM]

Rating

3

(a + b - c )(a + b + c );

= a^2 + ab - ac + ab + b^2 - bc + ac + bc - c^2;

= a^2 + b^2 - c^2+ 2ab

= a^2 + ab - ac + ab + b^2 - bc + ac + bc - c^2;

= a^2 + b^2 - c^2+ 2ab

Added 3/23/2016 11:45:24 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/8/2016 11:09:41 AM]

3

(ab - 9)(ab + 8);

= ab*ab - 9*ab + ab*8 - 9*8;

= a^2b^2 - 9ab + 8ab - 72;

= a^2b^2 - ab - 72

= ab*ab - 9*ab + ab*8 - 9*8;

= a^2b^2 - 9ab + 8ab - 72;

= a^2b^2 - ab - 72

Added 3/23/2016 11:46:16 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/8/2016 11:09:56 AM]

28,236,777

questions answered

There are no comments.